Dura’s Effect on Securities Class Actions - Duncan, Scotland M. (Journal of Law and Commerce, 2008)
On April 19, 2005, the United States Supreme Court rendered a unanimous decision in Dura Pharmaceuticals, Inc. v. Broudo, which had been described as “the most important securities case in a decade.” Simply put, the decision raises the pleading standard for Rule 10b-5 cases asserting fraud-onthe-market; instead of requiring a showing of ex ante losses, such as inflation at the time of purchase, Dura requires a showing of ex post losses, such as market decline resulting from a corrective disclosure. This paper assesses the decision’s practical implications by examining and empirically testing whether the Supreme Court’s enhanced pleading requirements have impacted the frequency and magnitude of post-Reform Act (PSLRA) class action securities cases. Specifically, this paper examines Dura’s effect on the filing and settling of cases, as well as on settlement amount. In particular, the results suggest that Dura, ceteris paribus, has had a statistically significant impact on both the filing and settlement of class actions, suggesting a reduction in frivolous litigation.